Nutritional and techno-functional properties of Australian Acacia seed flour: Effects of roasting on chemical composition, physicochemical properties, and in vitro digestibility and intestinal iron absorption. (February 2023) - Adiamo, Oladipupo Q.; Netzel, Michael E.; Hoffman, Louwrens C.; Gidley, Michael J.; Osborne, Simone; Sultanbawa, Yasmina
Graphical abstract: Highlights: Acacia seeds (AS) need varying roasting time (RT) to reduce trypsin inhibitor activity by 75%. A 7 min RT increased the protein digestibility in A. victoriae and A. coriacea by 36 and 61%, respectively. Intestinal iron absorption was not significantly affected by roasting. Ordered secondary structure decreased with increase in RT. Less adverse effects on functional properties were found in 7-min roasted AS as compared to commercial roasted AS flour (CRAS). Abstract: Acacia seed (AS) is rich in protein and iron but contains protease inhibitors that can reduce protein digestibility (PD). The seeds are generally roasted prior to consumption, although no information on the PD of roasted AS is available. This study investigated the effect of roasting time (5, 7 and 9 min at 180 °C) on the chemical composition, physicochemical properties, and in vitro PD and intestinal iron absorption of three wild harvested Australian AS species, Acacia victoriae, A. coriacea and A. cowleana . Roasting A. victoriae and A. coriacea seeds for 7 min significantly increased PD in the seeds by 36 and 61 %, respectively. A 9-min roasting time was required to achieve 75 % reduction in trypsin inhibitor activity in A. coriacea seed, while a shorter roasting time (RT) was sufficient to achieve similar reduction rates in the other two Acacia species. Among the functional properties, water and oil absorption capacities were significantly enhanced as RT increased. The starch granules in 7- and 9-min roasted A. victoriae seed flour detached from the protein matrix while random coil increased in 7-min roasted A. victoriae and 9-min roasted A. coriacea and A. cowleana, thus, contributing to enhanced PD. Although the SDS-PAGE in 7- and 9-min roasted A. cowleana samples showed reductions in the intensity of bands for high molecular weight proteins, PD was not affected by RT. However, intestinal iron absorption was not significantly affected by roasting as compared to raw digesta samples. Compared to commercial roasted Acacia seed, the considerably shorter RT used in this study improved PD in the AS flour with less adverse effects on techno-functional properties.